Benzodiazepine Withdrawal Catatonia, Delirium, and Seizures in a Patient With Schizoaffective Disorder - Mader, Edward C. (J Investig Med High Impact Case Rep, 2020)
Benzodiazepine withdrawal symptoms vary from mild anxiety to life-threatening delirium or seizures. In susceptible individuals, such as those with mood disorders, benzodiazepine withdrawal may also precipitate catatonia. A 26-year-old man with schizoaffective disorder (depressed type with catatonia) ran out of lorazepam and presented with catatonia, delirium, and seizures. He was taking olanzapine, venlafaxine, and trazodone for schizoaffective disorder. Lorazepam 2 mg twice daily kept him free of catatonia for 6 months. Besides catatonia and delirium, lorazepam withdrawal also triggered convulsive seizures and nonconvulsive status epilepticus. He was admitted to the intensive care unit where he underwent continuous video-EEG monitoring. Catatonia resolved with lorazepam on day 2. Seizures stopped with levetiracetam, lacosamide, and propofol on day 4. His mental status was normal when he was discharged on day 6. If not immediately recognized and treated, catatonia and delirium can lead to significant morbidity or mortality. Unfortunately, physicians tend to overlook catatonia and delirium, especially if both syndromes are present. At first, we suspected that our patient had ictal catatonia, but video-EEG showed no clear-cut correlation between catatonia, seizures, and epileptiform activity. As with prior observations, the patient’s catatonia was more sensitive to benzodiazepine withdrawal and treatment than his seizures. The efficacy of benzodiazepines in aborting catatonia, seizures, and mixed delirium-catatonia syndromes suggests a key pathogenetic role of abnormal GABA neurotransmission in these brain disorders.